Autopoietic system: New perspective in the development communication study - Widyastuti, Dhyah Ayu Retno; Wahyuni, Hermin Indah (Universitas Padjadjaran, 2024)
Background: Understanding the concept of development communication is necessary. The study of development communication has grown and tends to be dynamic in Africa and Asia. Any communication modifications are crucial, and they can serve as the starting point for the development history. Purpose: The research aimed to develop a new perspective for studying development communication. Methods: The research used a qualitative approach. It analyzed the evolution and history of concepts that developed in the study of development communication in Africa and Asia. The data were collected through a review of literature from various journals, books, and other publications relevant to development communication studies in Africa and Asia. The researchers used a literature review as a methodology, considering that knowledge production is getting faster. Besides, the researchers complemented the study on development communication among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia’s context. Results: The study showed that development communication is most relevant to developing countries such as Africa and Asia. Based on the best practice of MSME in DIY, the autopoietic system by Niklas Luhmann is essential as an innovative perspective in development communication study. The autopoietic approach emphasizes that the system will produce its components self-creation to reduce complexity. It consists of communication, evolution, and differentiation, which build up the autopoietic system. Conclusion: The logic of the autopoietic system, which negates humans, is still challenging to build awareness of communication significance as the core of development communication, not the actors. Implications: This idea suggests the impact of advancing communication studies, particularly future communication studies development.